GENETIC PARAMETERS OF GROWTH, CARCASS, AND LAYING TRAITS IN TWO LINES OF UKRAINIAN QUAIL - Jameela Hairan Salih (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
The estimation of genetic parameters of certain productive characters in different lines of quail is very important to make a breeding schedule for such lines of quail in the future. This study was carried out for three generations to estimate the response to selection, selection deferential, genetic, and phenotypic correlation between studied traits (growth and laying performance) and heritability estimates in two lines of Ukrainian quail (Coturnix coturnix coturnix). A total  of 120  Ukrainian  quails  from ) 500 ( quail birds   (base  population),  were   selected as parent generation for both lines and also 120 offspring birds specified for the third generation. The selection was based on body weight which was carried out on the 20th day of age. The results showed that the selection can improve breast weight, leg weight, carcass%, and live body weight in both lines. However, the realized heritability has moderate values for 42-day age body weight for both lines; but the dark line recorded a higher genetic correlation between body weight and weight gain compared to the white line. The highest phenotypic correlation estimates between body weight and egg weight were recorded for the white line; in addition, the same line receded better estimates for the studied genetic parameters in all other studied characteristics. It could be concluded that the selection based on the genetic parameters for growth and laying traits was effective for improving it through the three generations.